A novel passive shoulder exoskeleton for assisting overhead work. (2nd March 2023) - Ding, Shuo; Reyes Francisco, Anaya; Li, Tong; Yu, Haoyong
Abstract: Shoulder exoskeletons (SEs) can assist the shoulder joint of workers during overhead work and are usually passive for good portability. However, current passive SEs face the challenge that their torque generators are often attached to the human arm, which adds a significant amount of weight to the user's arms, resulting in additional energy consumption of the user. In this paper, we present a novel passive SE whose torque generator is attached to the user's back and assists the shoulder joint through Bowden cables. Our approach greatly reduces the weight on the user's arms and can accommodate complex shoulder joint movements with simple and lightweight mechanical structure based on Bowden cables. In addition, to match the nonlinear torque requirements of the shoulder joint, a unique spring-cam mechanism is proposed as the torque generator. To verify the effectiveness of the device, we conducted a usability test based on muscle activations of 10 healthy subjects. When assisting overhead work, the SE significantly reduced the mean and maximum electromyography signals of the shoulder-related muscles by up to 25%. The proposed SE contributes to further research on passive SE design to improve usability, especially in terms of reducing weight on human arms.